Development of Metacognition in Adolescence: The Congruency-Based Metacognition Scale - dos Santos Kawata, Kelssy Hitomi; Ueno, Yuki; Hashimoto, Ryuichiro; Yoshino, Shinya; Ohta, Kazusa; Nishida, Atsushi; Ando, Shuntaro; Nakatani, Hironori; Kasai, Kiyoto; Koike, Shinsuke (Frontiers in Psychology, 2021)
Introduction Previous studies on metacognitive ability were explored using self-report questionnaires that are difficult to adequately measure and evaluate when the capacity for self-reference is undeveloped. This study aimed to validate the Congruency-based Metacognition Scale (CMS) to measure metacognition and the feeling of confidence abilities, and to investigate the development of metacognition during adolescence. Methods The CMS was administered to 633 child-parent pairs (child, mean age = 16.0 years, 46.0% female; parent, mean age = 48.3 years, 94.9 % mother) in Japan. The CMS metacognition score was assessed based on congruency scores between the self-report of the child from a third-person perspective (3PP) and the parent’s report from the first-person perspective (1PP). The CMS self-judgement accuracy score was assessed by the congruency scores between the child’s self-report from the 1PP and 3PP. For both measures, the more distant the 3PP on the self-report was from the 1PP on the parents-report and child self-report, it means low ability. An exploratory factor analysis (EFA) was conducted to examine construct validity and then a confirmatory factor analysis (CFA) was used. Criterion validity was examined by calculating Pearson’s correlation coefficients with scores on the Beck Cognitive Insight Scale (BCIS) and Autism Quotient (AQ). We used intraclass correlation and Cronbach’s alpha to examine the test-retest and internal consistency reliability. Results Based on the results of the EFA and CFA, we adopted one factor structure with five items. The CMS metacognition and CMS self-judgement accuracy showed evidence criterion validity, exhibiting significant correlations with the BCIS self-reflectiveness (r = 0.16) and self-certainty scores (r = 0.17), respectively. Regarding to the AQ, only the CMS metacognition score had significant correlations with the social skills (r = 0.22) and total scale score (r = 0.20). The test-retest reliability showed adequate (intraclass correlation coefficient 0.70 to 0.81 and the Cronbach’s alpha coefficient 0.63 to 0.59). Adolescents were found to have significantly lower metacognitive ability compared to young adults. Conclusions CMS could be a valid and reliable measure to examine metacognitive abilities for adolescents.